Modelling the diversion of erratic boulders by the Valais Glacier during the last glacial maximum - Jouvet, Guillaume; Seguinot, Julien; id_orcid:0 000-0002-5315-0761; Ivy-Ochs, Susan; Funk, Martin (International Glaciological Society, 2017)
In this study, a modelling approach was used to investigate the cause of the diversion of erratic boulders from Mont Blanc and southern Valais by the Valais Glacier to the Solothurn lobe during the Last Glacial Maximum (LGM). Using the Parallel Ice Sheet Model, we simulated the ice flow field during the LGM, and analyzed the trajectories taken by erratic boulders from areas with characteristic lithologies. The main difficulty in this exercise laid with the large uncertainties affecting the paleo climate forcing required as input for the surface mass-balance model. In order to mimic the prevailing climate conditions during the LGM, we applied different temperature offsets and regional precipitation corrections to present-day climate data, and selected the parametrizations, which yielded the best match between the modelled ice extent and the geomorphologically-based ice-margin reconstruction. After running a range of simulations with varying parameters, our results showed that only one parametrization allowed boulders to be diverted to the Solothurn lobe during the LGM. This precipitation pattern supports the existing theory of preferential southwesterly advection of moisture to the alps during the LGM, but also indicates strongly enhanced precipitation over the Mont Blanc massif and enhanced cooling over the Jura Mountains. ISSN:0022-1430 ISSN:1727-5652